The Right to Question: Democratic Legitimacy and the Crisis of Electoral Trust in India (London Journal of Research In Humanities and Social Sciences, 2025)
This research paper aims to examine the basic principles of democratic governance, primarily focusing on the right of citizens to ask questions, a crucial mechanism for accountability. Drawing upon the Social Contract Theory, the study explores whether questions arising about the electoral system—a vital component of democracy—suggest a violation of the government’s responsibility and the terms of the contract with the people. Specifically, the paper analyzes public opinion regarding the democratic contract following the 2024 Indian parliamentary general elections, when serious allegations about electoral transparency emerged. It investigates the sovereign public’s actual perceptions of the allegations and counter-allegations among the Election Commission, the government, and the opposition, recognizing that these controversies not only fuel political dispute but also pose a significant challenge to public trust. Furthermore, the research examines how these events affect citizens’ faith in the electoral system and their future democratic participation. It also studies the perceived necessity of post-election scrutiny and the importance of addressing the public’s concerns to maintain democratic credibility. Ultimately, the paper argues that the longevity of a democracy depends not on the absence of questions, but on the system’s ability to resolve those questions transparently, thereby reaffirming the contract between the state and its citizens.
Keywords: Commission of India.; democratic accountability; Election; Electoral Reform; Public Trust; social contract